Factores de riesgo relacionado al síndrome de abstinencia neonatal en el Hospital General Guasmo Sur, periodo enero - mayo 2024. - Coello Loor, Lady Nayeli (2024)
Currently, drug use in pregnant women can cause complications in the newborn at the time of birth, such as neonatal abstinence syndrome, which is assessed using the Finnegan scale. The objective of the work was to identify risk factors related to neonatal abstinence syndrome. Method: For which the inductive, descriptive, quantitative, transversal and retrospective method was applied. For which the indirect observation collection technique was used and the observation matrix as an instrument. 98 neonates diagnosed with withdrawal syndrome were included. As a result, it was obtained that 74% are male and 26% female, 75% are between 1 to 3 days 85%. The perinatal history shows that 92% of the mothers had exposure to illicit substances before pregnancy, where 98% have consumed alcohol, heroin 64%, marijuana 23%, cocaine 20%, caffeine 7%, methamphetamines 6% and benzodiazepines 5%. They present a degree of severity of neonatal abstinence syndrome: severe 66.3%, moderate 22.4%; and mild 11.2%. Regarding complications, 98% present muscle hypertonia followed by excessively high -pitched crying in 89%. For vasomotor and respiratory metabolic alterations, 100% of neonates present nasal flaring. When analyzing the gastrointestinal manifestations, it is observed that 89% have loose stools followed by poor feeding 68% regurgitation 46% excessive suction 32% watery stools 12% and vomiting in project 1%. Conclusion: Withdrawal syndrome occurs in neonates of drug-dependent mothers such as heroin and cocaine.